Effect of air temperature, pH and nutrition on growth and sporulation of Ascochyta pisi - R. L. SUSURI; D. J. HAGEDORN; R. E. RAND (Acta Agriculturae Slovenica)
Isolates of Ascochyta pisi from diseased pea (Pisum sativum) varied greatly in growth rate, sporulation, mycelial appearance, physiology and pathogenicity. Best sporulation of A. pisi occurred on V-8 juice at 24oC, whereas best mycelial growth was on Czapeck medium and corn cockle (Agrostemma githago) seed meal agar. In pure culture on PDA A. pisi grew between 16 and 28oC with optimum at 24oC. Both isolates (A and P) grew well on medium with pH 3.8 to 7.3. As carbon sources maltose, dextrin and cellobiose supported best growth of isolates. Peptone, ammonium nitrate, ammonium sulphate and urea, as sources of nitrogen, promoted the best growth. The maximum vegetative growth is obtained with proline and casein hydroliysate for isolate A, whereas proline, aspartic acid and leucine as amino nitrogen sources for isolate P.